Use of electrochemical techniques to determine the effect of Sigma (σ)-phase precipitation on a 25 wt% Cr Super Duplex Stainless Steel. - Næss, M; Johnsen, R.; Iannuzzi, Mariano (NACE International, 2015)
Corrosion resistant alloys (CRA) for subsea pressure-retaining components must be compatible with production fluids and resistant to pitting and crevice corrosion in seawater. Whereas materials selection for production environments is governed by well-established standards such as ISO1 15156, debate still exists as of how to determine the seawater corrosion resistance of CRA.